2015
DOI: 10.1371/journal.pone.0116911
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage/Alteration of Interleukin-8 by Matrix Metalloproteinase-9 in the Female Lower Genital Tract

Abstract: ObjectiveInterleukin-8 (IL-8, CXCL8) plays important roles in immune responses at mucosal sites including in the lower genital tract. Since several types of bacteria produce proteases that cleave IL-8 and many types of bacteria can be present in lower genital tract microbiota, we assessed genital fluids for IL-8 cleavage/alteration.Study DesignGenital fluids collected by lavage from 200 women (23 HIV-seronegative and 177 HIV-seropositive) were tested for IL-8 cleavage/alteration by ELISA.ResultsIL-8 cleaving/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In AF, Cobo et al and Park et al have previously reported significant associations between AF IL-8 and MMP-9 with MIAC in women with PPROM [21,22]. Taken together, the data from our group and others [22,24,26] support the importance of MMP-9 and IL-8 in the common pathophysiology of MIAC and ruptured membranes, regardless of whether the source of these two proteins is CVF or AF.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In AF, Cobo et al and Park et al have previously reported significant associations between AF IL-8 and MMP-9 with MIAC in women with PPROM [21,22]. Taken together, the data from our group and others [22,24,26] support the importance of MMP-9 and IL-8 in the common pathophysiology of MIAC and ruptured membranes, regardless of whether the source of these two proteins is CVF or AF.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we demonstrated that CVF MMP-9 is a useful non-invasive biomarker for MIAC in PPROM, and that the CVF level of MMP-9 was also significantly correlated with CVF IL-8 (r = 0.410). Similarly, MMP-9 in the lower genital tract fluid has been shown to be involved in the cleavage of IL-8 at this mucosal site, suggesting MMP-mediated cleavage of IL-8 can modulate inflammatory responses in the lower genital tract [26]. In AF, Cobo et al and Park et al have previously reported significant associations between AF IL-8 and MMP-9 with MIAC in women with PPROM [21,22].…”
Section: Discussionmentioning
confidence: 96%
“…As one of the most widely investigated MMPs, MMP-9 is a significant protease which plays a vital role in many biological processes, such as wound healing [ 3 , 8 , 38 , 39 , 40 , 41 , 42 , 43 ]. This protease has a broad range of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…It can regulate the structure of ECM by cutting and degrading multiple extracellular matrix proteins through protease hydrolysis [18]. Apart from that, MMP-9 is capable of specifically cutting the extracellular domain on the surface of certain cell proteins to release them from the plasma membrane, and some peptides can also be degraded by MMP-9 outside the cell [19]. The basement membrane contains collagen, such as type IV collagen, so it can be degraded by MMP-9 [20,21].…”
Section: Introductionmentioning
confidence: 99%